2017
DOI: 10.1016/j.jss.2017.05.099
|View full text |Cite
|
Sign up to set email alerts
|

Enteric glial–mediated enhancement of intestinal barrier integrity is compromised by morphine

Abstract: Background The opioid epidemic is a growing concern and emerging evidence suggests that morphine use may be associated with sepsis. Enteric glial cells (EGCs) are the most numerous cell type in the enteric nervous system and regulate gastrointestinal function through the production of trophic factors, including Glial Derived Neurotrophic Factor (GDNF). We sought to determine the effect of morphine on enteric glia and hypothesized that morphine contributes to EGC dysfunction and increased gut permeability. Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 21 publications
1
27
0
Order By: Relevance
“…In agreement with this, PD patients show fecal biomarkers of inflammation as calprotectin and also increased intestinal permeability as alpha-1-antitrypsin [134]. It is known that the IEB is strongly regulated by EGCs [37][38][39]. Since EGCs is sensitized in PD patients and modulates all these processes, it is speculated that IEB could be impaired by altered glial signaling which could contribute to the inflammatory process.…”
Section: Parkinson's Diseasesupporting
confidence: 53%
See 1 more Smart Citation
“…In agreement with this, PD patients show fecal biomarkers of inflammation as calprotectin and also increased intestinal permeability as alpha-1-antitrypsin [134]. It is known that the IEB is strongly regulated by EGCs [37][38][39]. Since EGCs is sensitized in PD patients and modulates all these processes, it is speculated that IEB could be impaired by altered glial signaling which could contribute to the inflammatory process.…”
Section: Parkinson's Diseasesupporting
confidence: 53%
“…GDNF also inhibits apoptosis of EGCs in an autocrine manner [34]. Mu opioid receptor activation by morphine in EGCs decreases their GDNF synthesis, with consequent IEB disruption [39]. Moreover, GDNF has been shown to increase the integrity of the IEB via ZO-1 upregulation [38].…”
Section: Functions Of Egcs In Gut Homeostasis: Released Factors By Egmentioning
confidence: 99%
“…The EGC‐epithelial cell unit has also been associated with the anti‐inflammatory modulation of the immune system because EGC‐derived mediators such as GDNF, GSNO ( S ‐Nitrosoglutathione), and 15d‐PGJ2 (15‐Deoxy‐Delta‐12,14‐prostaglandin J2) support an intact epithelial barrier (Bach‐Ngohou et al, ; Neunlist et al, ; Neunlist et al, ; Pochard et al, ; Savidge et al, ), that in turn can dampen inflammation. A recent study of Baumann et al showed a reduced GDNF expression in EGCs in vitro after morphine treatment suggesting a role of EGCs in morphine associated sepsis (Bauman et al, ). As a consequence, a reduced transepithelial resistance in rat intestinal epithelial cells exposed to the supernatants of morphine‐treated EGCs compared to controls was detected.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, many predominant microbes in older animals correlate with CRP and neopterin, which again are generally markers of systemic immune activation and inflammation. It’s known that with age the permeability of the gut increases, allowing more bacterial products to translocate to the blood and promote inflammation (2, 11, 12, 30). Different bacterial products from different microbes could elicit stronger inflammatory responses in the blood, feeding back onto the gut to promote gut permeability.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, inflammatory cytokines in circulation increase with age, leading to chronic systemic inflammation that negatively affects the host’s ability to mount immune responses (1, 9, 10). Age-associated chronic inflammation also negatively affects organ function, such as in the gut where inflammation leads to increased gut permeability, or “leaky” gut (2, 11, 12).…”
Section: Introductionmentioning
confidence: 99%